Characterization and phylogenetic analysis of the complete mitochondrial genome of Eristalia cerealis (Diptera: Syrphidae) - Jingyan Yan; Shou Feng; Pengfei Song; Ying Li; Wangyan Li; Daoxin Liu; Xiuting Ju (Mitochondrial DNA. Part B. Resources, 2020)
The complete mitochondrial genome of Eristalia cerealis was sequenced and reported here. The circle genome of the syrphid fly is 15,348 bp in length. There are 38 sequence elements including 13 protein coding genes, 22 tRNA genes, 2 rRNA genes, and a control region. The order of all elements was the same with that of E. tenax. With 2 species from Muscidae and Drosophilidae as outgroups, phylogenetic relationships of 10 Syrphidae species based on mitogenomes were in complete agreement with their taxonomic relationships based on morphological characteristics. Our result will provide more fundamental data to the development of the molecular systematics of Syrphidae.